Two Decades of the Application of the Open Performance Review and Appraisal System in Tanzanian Local Government Authorities: A Synopsis of Predicaments and the Way Forward - Ndunguru, Geofrey; James, Ng’homange Merkiad; Gration, Justuce Muhoza (Local Administration Journal, 2024)
The Open Performance Review and Appraisal System (OPRAS), was introduced by the Tanzania government to manage employees’ performance and develop a performance management culture in the public sector (ministries, departments, agencies, and local government authorities). Local Government Authorities (LGAs) have been implementing this mandatory performance management tool since 2004. However, evidence suggests that the LGAs have not been able to create a genuine and effective OPRAS, despite the efforts taken to impose its implementation. In this regard, this study intended to provide an account of the predicaments experienced by the LGAs in OPRAS implementation and then recommend how LGAs can ensure effective implementation of the performance management system. A desktop review was employed complemented with interviews with 20 Human Resource and Administration Officers responsible for enforcing OPRAS implementation to inform the findings. The findings suggest that the LGAs have been trailing in the implementation of OPRAS due to numerous setbacks inter alia, employee skepticism of OPRAS, insufficient budget allocation, incompetence of staff in operating OPRAS, inadequate leadership commitment, and interference of political and contingent activities given the nature of decentralization of the LGAs. It is imperative to provide timely and adequate allocation of resources, improve leadership commitment, and ensure staff frequent staff capacity building for LGAs to implement a performance management system successfully.